GREEN PRODUCT REVOLUTION: TRANSFORMING HEALTH INFRASTRUCTURE THROUGH IDEATION AND IMPLEMENTATION - Zhang, Mei Lin; Al-Farsi, Abdullah (Research Journal of Health, Medicine and Nursing, 2024)
In response to escalating environmental concerns, numerous global companies have embarked on transformative initiatives, unveiling a wave of ‘‘sustainable,’’ ‘‘environmentally friendly,’’ or ‘‘ecofriendly’’ products through green product innovation schemes. Noteworthy examples include Ford's groundbreaking introduction of soy-based seat cushion foam, SC Johnson's proactive issuance of a green list outlining restricted ingredients for elimination, and Lipton Tea's commitment to sourcing 100% of their tea from environmentally sustainable estates. This paradigm shift in product development underscores a positive intent among companies, challenging the notion that environmental sustainability can be solely achieved through legislative measures. Instead, it posits that product innovation, coupled with the integration of cutting-edge technologies, plays a pivotal role in fostering sustainability (Berger et al., 2007). Drawing parallels, the construction industry, identified as a major contributor to global greenhouse gas emissions (Truitt, 2009) and the largest consumer of natural resources (USGBC, 2012), emerges as a sector with substantial potential to establish benchmarks and attain environmental and ecological sustainability (UN, 2015). This potential is anchored in the industry's ability to embrace green product innovation, reflecting a shift toward low energy consumption methods and an enhancement of resource efficiency in operational frameworks (Kibert, 2016). This paper explores the transformative landscape of environmentally conscious business practices, examining the motivations behind companies' adoption of green product innovation. By delving into the successes of notable initiatives in the automotive and consumer goods sectors, the paper sheds light on the positive intent and strategic foresight driving these sustainable shifts. Furthermore, it underscores the broader implications for industries like construction, where the adoption of similar innovation strategies can yield tangible progress in curbing environmental impact. The study advocates for a holistic approach that combines legislative frameworks with proactive and innovative measures to foster lasting environmental sustainability across diverse sectors.